PSORIASIS VULGARIS : LAPORAN KASUS - Fadila, Anisa (Universitas Tadulako, 2025)
Psoriasis is a common, chronic, non-communicable skin disease with an unknown cause. It causes inflammation of the skin that is long-lasting, persistent and permanent. To date, the cause of psoriasis remains unknown. A 30-year-old woman came with complaints of red spots accompanied by itching on both hands and feet. Complaints have been felt since 10 years ago. Complaints are aggravated when the patient consumes eggs, meat and nuts. Complaints are relieved when the patient scratches the wound area. The patient has a history of allergies to eggs, meat and nuts and there is no history of the same disease in the family. In this case, it was diagnosed based on anamensis physical examination such as examination of the wax drop phenomenon. Psoriasis vulgaris therapy in this case was given topical therapy as well as systemic drugs in the form of antihistamines and Vit D with a long treatment.